Turtle humeral microanatomy and its relationship to lifestyle. (August 2014) - Nakajima, Yasuhisa; Hirayama, Ren; Endo, Hideki
<x xml:space="preserve">Abstract</x> Among living turtles, highly terrestrial or highly aquatic modes of life are likely to have developed from a plesiomorphic semi‐aquatic one. A taxonomically comprehensive data set of turtle humeri was examined to ascertain if adaptation to an aquatic or a terrestrial lifestyle affects the general internal bone structure. Three‐dimensional and virtual cross‐sections were obtained from computed microtomography to compare humeral changes among the various lifestyles – terrestrial, semi‐aquatic and aquatic – focusing on the degree of resorption of periosteal bone. Regardless of lifestyle, the humeri of the 52 turtles examined lacked a large open medullary cavity, and only one or a few small cavity(ies) or intertrabecular spaces were found near the growth centre. Semi‐aquatic and aquatic turtles display the highest and lowest median values of humeral compactness, respectively, suggesting that limb‐bone lightening is acquired both in highly terrestrial and in highly aquatic turtles. The broad overlap in compactness values between the lifestyles and the lack of tubular structure in all turtles, however, suggest that selection pressure of skeletal lightening in terrestrial turtles is not high enough to cause a tubular structure, possibly because of the rather passive mode of locomotion in terrestrial turtles. This overlap also suggests that the humeral compactness could not be used alone to provide an indication of lifestyle in turtles. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 719–734.